2023
DOI: 10.3390/polym15040842
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Quantitative Analysis of Bicomponent Fibers Based on Cross-Sectional In-Situ Observation

Abstract: To accelerate the industrialization of bicomponent fibers, fiber-based flexible devices, and other technical fibers and to protect the property rights of inventors, it is necessary to develop fast, economical, and easy-to-test methods to provide some guidance for formulating relevant testing standards. A quantitative method based on cross-sectional in-situ observation and image processing was developed in this study. First, the cross-sections of the fibers were rapidly prepared by the non-embedding method. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Among existent studies, several works have focused on the characterization and the physico-chemical properties of these bicomponent filaments (PET/PTT) 8 11 . Indeed, recent studies investigated the effect of spinning parameters on the final structural of bicomponent filaments (PET/PTT) and the interfacial structure and binding forces between polytrimethylene terephthalate (PTT) and polyethylene terephthalate (PET) filaments using sophisticated analytical techniques 9 , 10 . Obtained results showed that during the spinning process, a distinct interface layer formed between PTT and PET, crucial for their binding.…”
Section: Introductionmentioning
confidence: 99%
“…Among existent studies, several works have focused on the characterization and the physico-chemical properties of these bicomponent filaments (PET/PTT) 8 11 . Indeed, recent studies investigated the effect of spinning parameters on the final structural of bicomponent filaments (PET/PTT) and the interfacial structure and binding forces between polytrimethylene terephthalate (PTT) and polyethylene terephthalate (PET) filaments using sophisticated analytical techniques 9 , 10 . Obtained results showed that during the spinning process, a distinct interface layer formed between PTT and PET, crucial for their binding.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of computer vision technology, a variety of methods have been proposed to automate profiled fibre detection [4, 5], classification [6–8] and shape factor estimation [9, 10]. Recently, many works focus on the recognition task which integrates detection and classification in a network.…”
Section: Introductionmentioning
confidence: 99%